"Give Sorrow Words": Working With Bereavement in Senior Residential Settings. Issue 11 (November 2015) - Aldrich, C. Knight
Abstract : Abstract: Bereavement and its consequent grief are frequent in senior residential settings. Failure to manage grief appropriately can have serious medical consequences, principally clinical depression. Focused talk with a grieving person can help ease the pain of grief; it can also help prevent complications that often lead to depression. Along with mental health professionals, staff members and volunteers can be important, and less expensive, participants in reaching this goal.